ON THE WAY OF DRAFTING THE CODE OF THE REPUBLIC OF KAZAKHSTAN ON ADMINISTRATIVE PROCEEDINGS: PREVENTION OF CORRUPTION IN THE FIELD OF ADMINISTRATIVE PROCEEDINGS - Marat Imangalievich, Жумагулов (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
Scientific article examines the nature of the administrative process, in relation to the judicial system. It describes the ways of codification of administrative procedure law